Mikroenkapsulasi Ekstrak Kulit Buah Naga Super Merah (Hylocereus costaricensis) pada Berbagai Massa Maltodekstrin dan Aplikasinya Sebagai Antioksidan: Microencapsulation of Super Red Dragon Fruit (Hylocereus costaricensis) in Various of Maltodextrin Mass and its Application as an Antioxidant - Sucianti; Nurhaeni; Jaya Hardi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Red super dragon fruit peel (Hylocereus costaricensis) extract has capability to scavenge DPPH and the activity could be maintained by using maltodextrin as coating. The aims of the research are to determine ratio of red super dragon fruit peel ethanol extract toward maltodextrin producing microcapsule with the highest coating efficiency and DPPH scavenging content by microcapsule of red super dragon fruit peel extract. Microencapsulation was carried out using freeze drying technique. Comparison of red super dragon fruit peel extract and maltodextrin were 1: 8, 1: 10, 1: 12, and 1:14 (w / w). The results show that the highest efficiency ratio of coating extract of red super dragon fruit peel with maltodextrin was 1: 8 with percentage of 90,77%. Level of DPPH scavenging content of red super dragon fruit peel extract microcapsule with ratio of 1:8 on 5 minutes and 60 minutes each is 27.36% and 46.62%. Keywords: Hylocereus costaricensis, freeze drying, maltodextrin, microencapsulation